Electrical stimulation of c2c12 cell culture as a model of human physical activity - Dyakova E.Yu.; Yun Yuyfen; Yugankina E.A.; Chernykh A.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to using a physical exercise model, evaluate the effect of electrical stimulation on the glucose transport mechanism of the C2C12 cell culture. Methods and structure of the study. For the study, the cells were randomly divided into 4 groups: 2 control groups and 2 experimental groups (with insulin resistance). Insulin resistance was formed using a high-glucose medium (25 mM). In each group, half of the cells were exposed to electrical stimulation, the other half remained intact. Half of the cells in each subgroup were treated with insulin to trigger the glucose transport mechanism. The content of the phosphorylated form of the Akt protein (pAkt) in the cells served as a marker for the operation of this mechanism. Results and conclusions. It was found that in cells with insulin resistance, pAkt was lower compared to the control group. The addition of insulin increased pAkt content, but its level in the experimental group remained reduced. Electrical stimulation increased the concentration of pAkt in all groups, bringing the level of this protein in the experimental groups to values ​​comparable to the control group. Physical activity is one of the methods for treating various diseases and improving both the psychological and functional state of the body. It has been proven that physical activity has a positive effect on the body with insulin resistance. Modeling physical activity on cell cultures using electrical stimulation makes it possible to elucidate the mechanisms of such positive effects.